Medicinal plants used by urban and rural inhabitants of Luziânia, Goiás, Brazil - Neves Delgado, Marina; Pinto Gome, Jessica s; Braz de Castro, Raphaela; Araújo de Sousa, Judite (Revista Agrogeoambiental, 2022)
The Brazilian flora is highly diverse, with the Cerrado biome featuring as the savanna with the highest richness of species in the world. Furthermore, the use of medicinal plants is a common and traditional practice among the Brazilian population. In that regard, it is expected that the populations of historical cities located in the Cerrado should have vast ethnobotanical knowledge. From this perspective, this study aimed to record the medicinal plants used by the inhabitants of Luziânia (GO), Brazil, and evaluate their socio-economic profiles. The inhabitants (18 from the urban area and 20 from the rural area) were selected by the ‘snowball’ technique and underwent semi-structured interviews that addressed socio-economic and ethnobotanical aspects. Among the interviewees, 74.4 % were women, with adults and older adults constituting the main connoisseurs, and 71 % had incomplete primary education. Most interviewees cultivated medicinal plants in their backyards and cited using leaves as the main plant organ for medicinal purposes. The interviewees from the urban and rural areas differed with regard to the form of obtaining knowledge (c2= 10,367; p < 0,05) since its origin was attributed to family transmission, reading, and from third parties in the urban area, whereas the rural inhabitants reported mainly family transmission. The interviewees cited 95 species, with no statistical difference between exotic and native species. However, the mentioned species were predominantly exotic. Lamiaceae, Asteraceae, and Fabaceae were the most representative families, and herbs were the most common type of medicinal plant. The most used species were Lippia alba (lemon balm), Mentha arvensis (mint), Dysphania ambrosioides (mastruz), and Plectranthus barbatus and Plectranthus grandis (boldo). The main health problems treated with medicinal plants were cold, indigestion, stress, and respiratory problems.